2017
DOI: 10.1128/genomea.01278-17
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequence of Saccharomycopsis fodiens CBS 8332, a Necrotrophic Mycoparasite with Biocontrol Potential

Abstract: Saccharomycopsis fodiens is an ascomycetous necrotrophic mycoparasite. Predator-prey interaction leads to killing of the host cell by a penetration peg and utilization of cell content by the predator. Here, we report the 14.9-Mb S. fodiens draft genome sequence assembled into 9 large scaffolds and 13 minor scaffolds (<20 kb).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
(10 reference statements)
0
5
0
Order By: Relevance
“…Similarly, the yeast-like Ustilaginomycete Pseudozyma aphidis parasitises the powdery mildew pathogen Podosphaera xanthii and B. cinerea (Calderon et al 2019; Gafni et al 2015). The genus Saccharomycopsis , comprising predacious yeasts directly feeding on their prey, was studied with respect to biocontrol of different Penicillium species as well as clinically relevant yeasts (Junker et al 2017, 2018, 2019; Lachance and Pang 1997; Pimenta et al 2008).…”
Section: Mechanisms Underlying the Biocontrol Activity Of Yeastsmentioning
confidence: 99%
“…Similarly, the yeast-like Ustilaginomycete Pseudozyma aphidis parasitises the powdery mildew pathogen Podosphaera xanthii and B. cinerea (Calderon et al 2019; Gafni et al 2015). The genus Saccharomycopsis , comprising predacious yeasts directly feeding on their prey, was studied with respect to biocontrol of different Penicillium species as well as clinically relevant yeasts (Junker et al 2017, 2018, 2019; Lachance and Pang 1997; Pimenta et al 2008).…”
Section: Mechanisms Underlying the Biocontrol Activity Of Yeastsmentioning
confidence: 99%
“…Just like we were unable to detect any genes in the sulfate assimilation pathway in the genomes of S . fodiens [27] and S . fermentans [28], the genes for sulfate uptake and reduction were all absent in the draft genome of S .…”
Section: Resultsmentioning
confidence: 99%
“…fermentans , but only one tRNA-CAG gene in the S . fodiens genome [27, 28]. We aligned these Saccharomycopsis tRNA(CAG) genes with serine and leucine tRNA genes from S .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a deeper understanding of the molecular biology of Saccharomycopsis species—specifically of their predacious behavior—is warranted. To this end, we recently established the draft genome of another predacious Saccharomycopsis yeast, S. fodiens strain CBS 8332 ( 9 ). We confirmed that, just like S. fibuligera , S. fodiens also lacks the genes in the sulfate assimilation pathway.…”
Section: Genome Announcementmentioning
confidence: 99%